A case of perforation of a pancreatic duct by a pancreatic stent during chemoradiotherapy for pancreatic head cancer: a case report - Takuya Mori; Go Ohira; Kenjiro Kimura; Sadaaki Yamazoe; Ryosuke Amano; Masaichi Ohira (Surgical Case Reports, 2019)
Abstract Background Pancreatic injuries are rare, and no treatment plan has yet been established for grade III injuries. In many cases, pancreatic stent placement has resulted in saving patients. However, some cases of perforation of a pancreatic duct during the placement of a stent have been described, and there are also a few cases of delayed perforation by a pancreatic stent. Case presentation A 62-year-old man had obstructive jaundice and pancreatitis due to locally advanced pancreatic head cancer. Both biliary and pancreatic stent were placed by endoscopy, after which chemoradiotherapy was performed. Four months later, he visited our hospital with severe abdominal pain. We performed enhanced CT and diagnosed the patient as having a perforation of a pancreatic duct by a pancreatic stent; therefore, we performed an emergency operation. Since we deemed pancreatectomy risky, we inserted pancreatic tubes into both sides of the perforated site and performed percutaneous transgastric drainage. The postoperative course was uneventful. We thereafter cut the tubes and switched to internal drainage. Conclusion Many cases of pancreatic injuries have reported that pancreatic stent placement results in saving the patient, but there have been few cases in which a pancreatic stent causes perforation of a pancreatic duct. External drainage by pancreatic tubes is very effective in resolving perforation of a pancreatic duct.